Glycothermal synthesis of Dy-doped Bi2MoO6nanoplates and their photocatalytic performance - Phattranit Dumrongrojthanath (2018)
© 2016 Springer Science+Business Media Dordrecht Dy-doped Bi2MoO6nanoplates with enhanced photocatalytic activities were successfully synthesized by a glycothermal method at 160 °C for 12 h. The products were characterized by X-ray diffraction, Raman spectroscopy, Fourier transform infrared spectroscopy, transmission electron microscopy, scanning electron microscopy, energy-dispersive X-ray spectroscopy, and UV–visible spectroscopy. In this research, 0–3 mol% Dy-doped Bi2MoO6products were orthorhombic Bi2MoO6nanoplates with an energy gap of 2.69–2.96 eV. The 3 mol% Dy-doped Bi2MoO6nanoplates show the best performance for photocatalytic degradation of rhodamine B of 97.22 % under visible-light irradiation within 80 min and can be used for wastewater treatment.